Environmental Health Socialization to Create a Healthy Village in Dasan Geria Village, West Lombok - Rahayu, Rachmawati Noviana; Suripto; Siti Raudhatul Kamali; Supardiono; Baiq Fadila Arlina; Natacha Amalia (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Hygiene and sanitation are inseparable components of environmental health. Gegutu Reban Hamlet, Dasan Geria Village, is one of the areas in West Lombok facing challenges in sanitation management due to the annual increase in population due to the clearing of agricultural and plantation land for new settlements. The main problem currently being faced is low public awareness and knowledge of environmental health, which results in low active participation in managing environmental sanitation. Furthermore, standard operating procedures for hygiene and sanitation in the village do not exist and have never been established. For this reason, community service activities were carried out with the aim of increasing awareness, knowledge and the level of active participation of the community in managing environmental health in Gegutu Reban Hamlet, Dasan Griya Village, West Lombok. The activities were carried out using lecture, focused groupe discussion, demonstration, practice and ongoing mentoring methods for the target audience, which included housewives, farmer representatives and youth representatives. The monitoring results showed that participants were very enthusiastic about participating in this activity. Participants' awareness and knowledge about maintaining environmental health increased. The accuracy of participants' skills in carrying out several practiced hygiene and sanitation actions also increased. This activity also produced a draft SOP for hygiene and sanitation management that can be implemented by local residents, especially in Gegutu Reban Hamlet, Dasan Griya Village, West Lombok.